Extended confiscation in criminal law : national, European and International perspectives / Malin Thunberg Schunke. - Thunberg Schunke, Malin (Series Supranational criminal law, 2017)
Extended Confiscation in Criminal Law provides a comprehensive analysis of the most recent developments in the field. With its main focus on the EU, this multi-faceted study enhances the reader's understanding of the strategy of confiscating assets, giving detailed answers to the questions of how the confiscation regimes could be improved and which changes are proportionate to the objectives pursued. The book begins by examining extended confiscation from the national perspective, presenting the substantive criteria for this power of confiscation. It focuses on three main jurisdictions - England and Wales, Germany and Sweden - and explores how domestic legislation is drafted and applied in their differing models. Analysing Directive 2014/42/EU on the Freezing and Confiscation of Instrumentalities and Proceeds of Crime in the European Union, it seeks to answer the questions of whether harmonisation truly increases efficiency or if other reforms may be more effectively. Furthermore, this book considers whether increased powers of extended confiscation strike the right balance between the interest of law enforcement and the protection of fundamental human rights. The notion of extended confiscation is then set in its broader context, looking from an international perspective. A holistic analysis of the regime for handling transnational confiscation cases is given, asking if it is possible to trace and search for assets abroad, or execute final orders in other states. This book is of great interest for academics as well as national and international legislators. It may also be used as a handbook for practitioners handling cross-border confiscation cases. DR MALIN THUNBERG SCHUNKE is an Associate Professor in Criminal Law at the University of Uppsala. She holds an LLD in Criminal Law (Uppsala University) and an LLM in Criminology and Criminal Justice (King's College, London). Her research interests lie in national and international criminal law, particularly EU judicial cooperation in criminal matters and human rights. She has been an Apprentice Judge at Stockholm City Court and has been working for several years as an Assistant Prosecutor at the Prosecuting Office Stockholm. 2 Intersentia